2001
DOI: 10.1007/s11916-001-0044-8
|View full text |Cite
|
Sign up to set email alerts
|

Postdural puncture headache: The role of prophylactic epidural blood patch

Abstract: Prophylactic epidural blood patch may prevent postdural puncture headache that develops after intentional or inadvertent dural puncture. However, despite earlier reports that this procedure was of value, subsequent studies have failed to show it has significant advantages over delayed blood patch. Reports that were supportive of this technique were based on nonrandomized observational studies with significant selective bias. At the present time, most centers do not routinely offer prophylactic blood patches, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…1 The best and most recent trial only included dural puncture with a 17-gauge Tuohy needle, used a sham injection in the control group, 20 mL of blood, blinded observers and lengthy follow-up. 17 This trial found a similar incidence (approximately 60%), similar severity but a shorter duration of PDPH in those who had received PEBP. Therapeutic EBP was required by about 50% of each group, which is consistent with recent observational series.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…1 The best and most recent trial only included dural puncture with a 17-gauge Tuohy needle, used a sham injection in the control group, 20 mL of blood, blinded observers and lengthy follow-up. 17 This trial found a similar incidence (approximately 60%), similar severity but a shorter duration of PDPH in those who had received PEBP. Therapeutic EBP was required by about 50% of each group, which is consistent with recent observational series.…”
mentioning
confidence: 69%
“…15 After PEBP, headache rates vary widely, from only 5-20% 1 to 40-80% 5,6,16 compared with 75-90% if no action is taken. So why do other reviewers disagree, 17 and why do the majority of academic units in North America, UK and Europe not routinely offer PEBP? The popularity of PEBP has fallen further, a very recent survey from the UK finding it used in only 3% of units.…”
mentioning
confidence: 99%
“…10,12 However, EBP is an invasive treatment as compared with other treatment modalities including theophyllines, caffeine, sumatriptan, and epidural saline. 13,14 It may contribute to back pain, lumbar vertebral syndrome, and transient bradycardia, and has been associated with an increase in body temperature. 15 Additionally, while EBP success rate is reported to approach 92% because of the introduction of blood into the epidural space, the patient may complain of immediate back pain, neckache, and radicular pain.…”
Section: Discussionmentioning
confidence: 99%
“…9 Nevertheless, epidural blood patch (EBP) is, to date, the most effective treatment for PDPH 7,10-12 when compared with other treatment modalities. 13,14 However, EBP is an invasive treatment that is not a benign procedure as it may contribute to the development of back pain, lumbar vertebral syndrome, transient bradycardia, and an increase in body temperature. 15 Untreated PDPH can result in serious complications such as subdural hematoma and seizures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation